Holding on and holding out : Jewish diaries from wartime France - Freadman, Anne, 1944- (University of Toronto Press, 2020)
"Examining the diary as a particular form of expression, Holding On and Holding Out provides unique insights into the experience of Jews during World War II in France. Unlike memoirs and autobiographies that reconstruct particular personal events, diaries, by contrast, record daily events without the benefit of retrospect and describe events as they unfold. This book assess how each individual used the diary to record their daily life under persecution; each was waiting for some end, be it with hope or despair. Each individual used the diary to bear witness not only to the terror of their own lives, but also to the lives and suffering of others. Several used their writing as a memorial to people who were killed. All use their writing to assert: I live, I will have lived. The book concludes by considering each diarist as selves in history, investigating how their reflections on their experience are informed by the times in which they had lived before the advent of persecution."--